2008
DOI: 10.1007/s00251-008-0328-9
|View full text |Cite
|
Sign up to set email alerts
|

Ovine progressive pneumonia provirus levels associate with breed and Ovar-DRB1

Abstract: Previous studies initiated defining the role of host genetics in influencing the outcome of exposure to ovine progressive pneumonia virus. However, specific genes influencing host control of virus replication and disease progression have not been identified. This study, using 383 ewes of the Columbia, Polypay, and Rambouillet breeds, tested the hypothesis that host control of OPPV as measured by provirus levels in the peripheral blood associates with certain breeds and MHC class II Ovis aries (Ovar)-DRB1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 29 publications
2
78
1
2
Order By: Relevance
“…MHC class II allelic variants have been associated with susceptibility/ resistance to several infectious diseases in DS, cattle, humans and chicken (Allen et al, 1996;Carrington and O'Brien, 2003;Dawkins et al, 1999;Herrmann-Hoesing et al, 2008;Hill et al, 1991;Zekarias et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…MHC class II allelic variants have been associated with susceptibility/ resistance to several infectious diseases in DS, cattle, humans and chicken (Allen et al, 1996;Carrington and O'Brien, 2003;Dawkins et al, 1999;Herrmann-Hoesing et al, 2008;Hill et al, 1991;Zekarias et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that although SRLV viral load is positively correlated with lesion severity in the host, significant breed differences in proviral concentrations indicate a host genetic component in susceptibility. 5,6 Although complete resistance would be the ideal host genetic trait, genetics that enable the host to maintain low viral load would be beneficial to decrease the overall consequence of disease. Maintenance of a low viral load may also be beneficial by decreasing risk of transmission to susceptible hosts.…”
Section: Host Geneticsmentioning
confidence: 99%
“…70 Recently, the genotypes of the major histocompatibility complex (MHC) class II DRB1 alleles and chemokine receptor 5 (CCR5) were evaluated within the context of OPPV peripheral blood provirus loads. 41,80 The MHC class II DRB1 was evaluated because previous literature suggested that MHC class II was a putative receptor for VISNA and possibly CAEV (Hullinger GA: 1993, A gp135 cellular receptor mediates infection of caprine synovial membrane cells by the lentivirus caprine arthritisencephalitis virus. PhD dissertation.…”
Section: Molecular Diagnostic Tests On the Small Ruminant Hostmentioning
confidence: 99%